2014 International Conference on Advances in Green Energy (ICAGE) 2014
DOI: 10.1109/icage.2014.7050135
|View full text |Cite
|
Sign up to set email alerts
|

PSO based controller algorithm for optimal allocation & setting of fuel cell in a wind — PV integrated power system for maximizing loadability

Abstract: Distributed Generators are gaining widespread applications around the world to facilitate the need for expanding generation capacity to meet the increasing load demand. However the integration and high penetration of distributed generations into the power system poses many issues that need to be addressed carefully. The main limiting factors for synchronous operation of distributed generators are voltage and angle instability and grid control authorities are limiting the distributed generator penetration level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Stochastic algorithms based methods were applied for selecting the suitable sizing and setting of shunt FACTS controllers to enhance the voltage stability [3][4][5][6][7][8][9] . Application of Genetic Algorithm (GA) for solving a range of power system problems has been reported in the literature [8][9][10][11] .…”
Section: Indices and Sets I Jmentioning
confidence: 99%
“…Stochastic algorithms based methods were applied for selecting the suitable sizing and setting of shunt FACTS controllers to enhance the voltage stability [3][4][5][6][7][8][9] . Application of Genetic Algorithm (GA) for solving a range of power system problems has been reported in the literature [8][9][10][11] .…”
Section: Indices and Sets I Jmentioning
confidence: 99%
“…The authors have presented a multi-objective function that incorporates network losses, bus voltage and energy cost in their work [39,40]. The utilization of a particle swarm optimization (PSO) algorithm has been documented in previous studies [41,42]. Previous research have shown the application of a genetic algorithm (GA) [43,44].…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the proposed method can reduce grid-connected wind power fluctuations and limit system faults in power generation. Joseph et al [25] proposed the use of a PSO method to maximize the system loadability within stability margins. Results showed that PSO improved the load carrying capacity when compared to the controller system installed in the plant.…”
Section: Introductionmentioning
confidence: 99%